NSAID-Induced Enteropathy in Rheumatoid Arthritis Patients with Chronic Occult Gastrointestinal Bleeding: A Prospective Capsule Endoscopy Study. (7th December 2013) - Tachecí, Ilja; Bradna, Petr; Douda, Tomáš; Baštecká, Drahomíra; Kopáčová, Marcela; Rejchrt, Stanislav; Bureš, Jan
Abstract : Background . The purpose of study was to evaluate the diagnostic yield of capsule endoscopy for NSAID-induced enteropathy and clinical, laboratory, and endoscopic characteristics of disease in patients with rheumatoid arthritis. Methods . 37 rheumatoid arthritis patients (30 women; mean age 55) treated with NSAIDs (>1 month), presented with anaemia and/or positive faecal occult blood testing, entered the study and underwent capsule endoscopy (EndoCapsule; Olympus), laboratory tests, and filled in questionnaires. Results . The prevalence of NSAID-induced enteropathy diagnosed by capsule endoscopy was 68% (25/37), classified as mild (red spots or erosions) in 18 (49%), moderate (10–20 erosions) in 4 (11%), and severe enteropathy (>20 erosions or ulcers) in 3 (8%) patients. We did not find statistically significant relationship between the enteropathy and gender, age, haemoglobin, leukocytes, albumin and CRP, or dyspepsia. The difference between subgroups of NSAIDs according to the COX specificity was not statistically significant. Conclusions . Capsule endoscopy is a highly accurate noninvasive method for evaluation of NSAID-induced enteropathy. It was revealed in a substantial section of the patients with rheumatoid arthritis and occult gastrointestinal bleeding, mostly classified as mild damage. No simple clinical or laboratory markers of the presence or severity of NSAID-induced enteropathy were recognised. This trial is registered with DRKS00004940 .